2018
DOI: 10.1038/s41598-018-27555-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Human Leptospirosis in a Clinical Setting: Real-Time PCR High Resolution Melting Analysis for Detection of Leptospira at the Onset of Disease

Abstract: Currently, direct detection of Leptospira can be done in clinical laboratories by conventional and by real-time PCR (qRT-PCR). We tested a biobank of paired samples of serum and urine from the same patient (202 patients) presenting at the hospital in an area endemic for leptospirosis using qRT-PCR followed by high resolution melting (HRM) analysis. The results were compared with those obtained by conventional nested PCR and with the serologic gold standard microscopic agglutination test (MAT). Differences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 31 publications
1
35
1
1
Order By: Relevance
“…Performing PCR on samples from both anatomical sites (blood and urine) allowed the diagnosis of 15 patients, while only 11 patients would have been diagnosed if only tested on blood and 12 if only tested on urine ( Figure 1 ). These results are in agreement with a previous work from Esteves et al where main cases were diagnosed at an early stage of the infection corresponding to dissemination and kidney colonization [ 22 ]. Thus, sampling on only one site would have left respectively 4 or 3 patients, respectively, with negative PCR results.…”
Section: Discussionsupporting
confidence: 94%
“…Performing PCR on samples from both anatomical sites (blood and urine) allowed the diagnosis of 15 patients, while only 11 patients would have been diagnosed if only tested on blood and 12 if only tested on urine ( Figure 1 ). These results are in agreement with a previous work from Esteves et al where main cases were diagnosed at an early stage of the infection corresponding to dissemination and kidney colonization [ 22 ]. Thus, sampling on only one site would have left respectively 4 or 3 patients, respectively, with negative PCR results.…”
Section: Discussionsupporting
confidence: 94%
“…For the rrs gene, subgroup analysis revealed that nested PCR assays targeting the gene are superior over other tests and slightly better than qPCR, as exhibited by the higher DOR and AUC of the SROC curve. In a previous study, qRT-PCR assay targeting the rrs gene was compared against nested PCR assay of the same gene, and the diagnostic performance was comparable between the two [72]. Another study on the detection of Strongyloides stercoralis also found that nested PCR shows better diagnostic sensitivity than real-time PCR [73].…”
Section: Discussionmentioning
confidence: 99%
“…Informed written consents were obtained, and about 10 millilitres of blood was collected from each subject for PCR. PCR was chosen over MAT because it is more sensitive and specific for leptospirosis detection [10]. DNA was extracted from serum samples using a DNeasy blood and extraction kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%